Performance quantification of Wireless Sensor Networks by implementing ZRP - Singh, Barjinder; Chawla, Rishma (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
sensor network is composed of a largenumber of autonomous sensor nodes, which are denselydeployed in the area of interest i.e either inside thephenomenon or very close to it. Routing is an importantoperation, being the foundation of data exchangingbetween wireless devices.Zone Routing Protocol was thefirst hybrid routing protocol with both a proactive and areactive routing component. ZRP was proposed to reducethe control overhead of proactive routing protocols anddecrease the latency caused by route discovery in reactiverouting protocols. ZRP defines a zone around each nodeconsisting of the numbers of neighbourhood. During myresearch work, I applied the hybrid routing protocol inwireless sensors and measure the correspondingperformance of the network in terms of overhead, delayand throughput.[10]